Complementary feeding in preterm infants: a position paper by Italian neonatal, paediatric and paediatric gastroenterology joint societies - Maria Elisabetta Baldassarre; Raffaella Panza; Francesco Cresi; Guglielmo Salvatori; Luigi Corvaglia; Arianna Aceti; Maria Lorella Giannì; Nadia Liotto; Laura Ilardi; Nicola Laforgia; Luca Maggio; Paolo Lionetti; et al. (BMC, 2022)
Abstract Nutrition in the first 1000 days of life is essential to ensure appropriate growth rates, prevent adverse short- and long-term outcomes, and allow physiologic neurocognitive development. Appropriate management of early nutritional needs is particularly crucial for preterm infants. Although the impact of early nutrition on health outcomes in preterm infants is well established, evidence-based recommendations on complementary feeding for preterm neonates and especially extremely low birth weight and extremely low gestational age neonates are still lacking. In the present position paper we performed a narrative review to summarize current evidence regarding complementary feeding in preterm neonates and draw recommendation shared by joint societies (SIP, SIN and SIGENP) for paediatricians, healthcare providers and families with the final aim to reduce the variability of attitude and timing among professionals.